Improving female physician's careers in academic medicine: Chances and challenges. Issue 1 (March 2018) - Pfleiderer, Bettina; Bortul, Marina; Palmisano, Silvia; Rodde, Sibyll; Hasebrook, Joachim
Abstract : University hospitals are involved in the care of critically ill patients, pregraduate and postgraduate education, and medical research with an increasing demand on physicians due to a higher burden of disease. The number of female physicians is increasing; however, young female physicians are less willing to work at university hospitals under the given conditions. They often do not find appropriate working conditions in mostly hierarchically structured university hospitals. Institutional structures involuntarily erect barriers against the recruitment, retention, and career progression of women. Gendered working conditions remain firmly fixed, and this is even more challenging – overt discrimination has been replaced by less visible mostly implicit stereotypes and prejudices against women. Having children is an additional "career stopper" for female physicians: those with children are less likely to be promoted and have a lower income. Regulatory measures should act in several directions: cultural gender equality policies, family support policies, and active work policies.